Duration of initial prednisolone therapy for first episode of childhood nephrotic syndrome based on time to response - Xiaoshan Tang; Qian Shen; Jia Rao; Jing Chen; Xiaoyan Fang; Zhiqing Zhang; Manpreet Grewal; Tej Mattoo; Hong Xu (Frontiers in Pediatrics, 2022)
BackgroundThe duration of initial corticosteroid therapy in newly diagnosed Idiopathic nephrotic syndrome (INS) is about 3 months. Our study was designed to test the feasibility of a shorter duration of corticosteroid therapy in newly diagnosed INS who show a quicker response.MethodsPatients who responded within 10 days (Group A) received 8 weeks of corticosteroid therapy as compared to 12–14 weeks of standard therapy in those who responded between >10 days to 28 days (Group B), and follow up for 52 weeks. The primary endpoint is time to first relapse after treatment completion. (NCT03878914, March 18, 2019)ResultsA total of 33 children with INS were enrolled and the follow-up data were analyzed. The clinical and laboratory characteristics of patients in both groups were similar. No significant difference was found in time to first relapse [65(14.5, 159) days for Group A vs. 28(17, 61.5) days for Group B, P = 0.371], the incidence of frequently relapsing nephrotic syndrome [6/18 (33.3%) vs. 5/10(50%), P = 0.644] or requirement for alternative immunosuppressant [4/18 (22.2%) vs. 1/10 (10%), P = 0.769]. Group A received similar corticosteroid dose compare with Group B (3511 ± 2421 mg/m2 vs. 4117 ± 2556 mg/m2, P = 0.524). Frequency and severity of corticosteroid-related complications was similar in both groups.ConclusionsThe time to first relapse and the number of relapses per patient were comparable between the two groups. However, more patients in Group A relapsed and the mean total dose of prednisolone for the study period was very similar between the two groups.